2014
DOI: 10.1371/journal.pone.0085428
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Bacterial Annexins – Putative Ancestral Relatives of Eukaryotic Annexins

Abstract: Annexins are Ca2+-binding, membrane-interacting proteins, widespread among eukaryotes, consisting usually of four structurally similar repeated domains. It is accepted that vertebrate annexins derive from a double genome duplication event. It has been postulated that a single domain annexin, if found, might represent a molecule related to the hypothetical ancestral annexin. The recent discovery of a single-domain annexin in a bacterium, Cytophaga hutchinsonii, apparently confirmed this hypothesis. Here, we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…Annexins belong to a diverse multi-gene, multi-functional family of proteins (Moss et al, 2004;Clark et al, 2012, Yadav et al, 2018. They have been identified in fungi (Grenville-Briggs et al, 2010;Khalaj et al, 2015) plants, animals, aarchaea and also in prokaryotes (Kodavali et al, 2014). Annexin superfamily has been grouped into seven subfamilies, which are designated as ANNXA to ANNXG.…”
Section: Introductionmentioning
confidence: 99%
“…Annexins belong to a diverse multi-gene, multi-functional family of proteins (Moss et al, 2004;Clark et al, 2012, Yadav et al, 2018. They have been identified in fungi (Grenville-Briggs et al, 2010;Khalaj et al, 2015) plants, animals, aarchaea and also in prokaryotes (Kodavali et al, 2014). Annexin superfamily has been grouped into seven subfamilies, which are designated as ANNXA to ANNXG.…”
Section: Introductionmentioning
confidence: 99%
“…They are expressed by all living organisms, from protists to higher eukaryotes and plants, but with the exception of bacteria. However, the group of Fernandez and Morgan first reported the presence of a gene coding for a single domain annexin in the bacteria Cytophaga hutchinsonii, although the protein is not expressed (Morgan et al, 2006) and a broader survey of bacterial genomes has identified around 30 annexin homologs, including single-domain and multi-domain annexins in 17 bacterial species (Kodavali et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Administration of giardin to mice induced protective immunity against Giardia and is under investigation for its vaccine potential (8). The Burkholderia JOSHI_001 protein possesses both a colicinD toxin domain and an annexin domain (9), which reinforces the notion that microbial annexins contribute to microbial virulence.…”
Section: Introductionmentioning
confidence: 58%
“…A recent review revealed a paucity of studies about microbial annexins, but the available information suggests that these proteins are critical for the virulence of certain pathogens (8, 9). Giardin from Giardia (10) is an immunodominant annexin protein (11).…”
Section: Introductionmentioning
confidence: 99%